AN ANALYTICAL APPROACH FOR FORENSIC COMPARISON OF SOIL SAMPLES OF DELHI REGION (Journal of Forensic Medicine & Toxicology, 2024)
Introduction: Soil serves as valuable trace evidence in forensic investigations due to its unique properties and transferability Soil is important trace evidence due to its unique geo-marker property and morphological structure because each type of soil has precise habitats that act as identification markers. This heterogeneity is the ability to compare and identify two different soil types. Hence, the availability of soil databases of different areas of a particular region can be of utmost importance in the crime scene investigation.
Keywords: Composition; Microscopic Examination; Soil; Trace Evidence; XRF